KONSISTENSI TERMINOLOGI, INVENTARISASI POTENSI DAN PENGUATAN INFRASTRUKTUR DALAM UPAYA PELESTARIAN KRIYA - Guntur, Guntur (Institut Seni Indoensia Surakarta, 2010)
As the activities and products of the oldest arts, crqï¬‚ should have a reliability of conceptual art, bothÂ among the general population and even mone so in education. However; in reality it still shows the use ofÂ terminology no consistency Ironically, this occurred at a govemment institution that organizes educationalÂ programs in the ï¬eld of craft. Conservation eï¬nrts should be initiated to foster one of the pmblern. InÂ addition to strengthening the existing infmstructure in craft world.Key wards: craft, conservation, consistency, and infrastructure